Mujer y religión: la "méter" en el umbral del III milenio - Iriarte, Ana (Studia Historica. Historia Antigua, 2010)
RESUMEN: La problemática del culto a las antiguas diosas como vía de integración política para la mujer griega ayudará a contextualizar la polémica figura de la Meter que Atenas acoge en su agora. Una figura al tiempo nebulosa y persistente, cuyas huellas pueden detectarse en fenómenos culturales de nuestra época. ABSTRACT: The problematics involved in the cult of the ancient goddesses as a means of political integration for Greek women will help to contextualize the polemical figure of the Metroum that Athens harboured in its agora. It was a figure at the same time nebulous and persistent, whose traces can be detected in the cultural phenomena of our time.